POETIC TRANSLATION AND STUDENTS’ APPRECIATION THROUGH HUMAN TRANSLATOR AND MACHINE SYSTEM - Pudjiati, Danti; Mulatsih, Maria Vincentia Eka; Ilham, Ilham; Darta, Deta Maria Sri; Suhel, Febrio Rahim (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
The engagement with poetry is a personalized journey that transcends standardized methodologies. Key to this process is complete immersion in the poetic experience, alongside evaluators’ openness to both human and machine-generated translations from Indonesian to English. The overarching goal is to enhance students’ discernment and appreciation of these translated works. The study’s specific objectives involved comparing poetic translation assessments by evaluators for both human translators and machine systems. It was to assess students’ appreciation of poetry through the lens of both translation methods across three different institutions. The research employed a mixed-methods approach, combining quantitative and qualitative descriptive analyses, including descriptive statistics. The dataset comprised two Indonesian poems by Taufik Ismail, rated using a score as proposed by Nababan. Findings indicate that human translators outperformed machine systems in terms of accuracy, acceptance, and readability. While students from Institutions 1 and 2 preferred human-translated poetry, students from Institution 3 favoured machine-translated versions. This suggests that human translation quality remains superior.